TIDAK ADA HUBUNGAN ANTARA DURASI PEMBERIAN OKSIGEN MELALUI NASAL KANUL NON HUMIDIFIER DENGAN INSIDEN IRITASI MUKOSA HIDUNG PADA PASIEN DI ICU - Nuryanti Sindif; Muhamat Nofiyanto; R Anggono Joko Prasojo (Universitas Jenderal Achmad Yani Yogyakarta, 2014)
Background: Oxygen administration is given to patients have oxygen supply deficit during observation due to trauma or respiratory disorder. Oxygen may be administered through a low flow method, i.e. nasal cannula. The use of non humidifier nasal cannula may cause the incidence of nasal mucosa irritation. Administering oxygen through non humidifier nasal cannula should be stopped when the oxygen therapy is more than 5 litre per minute. Objective: To investigate the correlation between the duration of non humidifier nasal cannula oxygen use and the incidence of nasal mucosal irritation at ICU in Panembahan Senopati Hospital Bantul. Method: This was an observational study which used a quantitative method, with correlational design and cross sectional approach. Samples were purposively selected comprising as many as 31 people. Data were obtained from observation sheet and analyzed with Fisher’s Exact test. Result: The use of non humidifier nasal cannula oxygen was mostly in short duration (58.1%). The majority of patients did not encounter the incidence of nasal mucosal irritation (96.8%). The result of Fisher’s Exact test showed p=0.419 >0.05. Conclusion: There was no significant correlation between the duration of non humidifier nasal cannula use and the incidence of nasal mucosal irritation in the ICU patients at PanembahanSenopatiHospital Bantul. Keywords: Duration of use, oxygen, non humidifier nasal cannula, nasal mucosal irritation